Hasdai Crescas & Leone Ebreo on Love and Joy - Harvey, Warren Zeev (Anales del Seminario de Historia de la Filosofía, 2024)
Rabbi Hasdai Crescas’ discussion of God’s joy (simḥah) in his Light of the Lord, Book I, Part 3, Chapter 5, had a marked influence on the discussion of God’s joy (la delettazione) by Rabbi Judah Abrabanel, alias Leone Ebreo, in his Dialogues of Love, Dialogue III. Leone, following Crescas, holds that God’s joy is active not passive; that it is mentioned in Psalms 104:31; and that it is also mentioned in BT Kebubot 8a. Moreover, Leone, like Crescas, cites Genesis 6:6, which attests to God’s sadness. Leone’s theories concerning God’s joy and love reflect his reading of Crescas.